2016
DOI: 10.1016/j.coviro.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus sensing by the immune system

Abstract: The host immune system developed multiple ways for recognition of viral pathogens. Upon disseminated adenovirus infection, the immune system senses adenovirus invasion from the moment it enters the bloodstream. The soluble blood factors, FX, antibodies, and complement, can bind and activate plethora of host-protective immune responses. Adenovirus binding to the cellular β3 integrin and endosomal membrane rupture trigger activation of IL-1α/IL-1R1 proinflammatory cascade leading to attraction of cytotoxic immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…However, AAV-based strategies are cautioned by increasing reports of unintended and potentially hazardous off-target integration events [ 53 58 ]. Despite a well-characterized immune response to adenoviral vectors [ 59 ] and a likely in vivo immune response against Cas9 per se [ 60 ], our work showed that knock-in gene editing via adenoviral vector is efficient enough to persist over time and did not have overt detrimental effects on the animals' health. Our results, taken with an overall lack of mortality in the study, allow the conclusion that adenovirus vector-mediated knock-in was well tolerated in the animals, contrary to a previous report of adenovirus as unsuitable for therapeutic gene editing [ 12 ].…”
Section: Discussionmentioning
confidence: 80%
“…However, AAV-based strategies are cautioned by increasing reports of unintended and potentially hazardous off-target integration events [ 53 58 ]. Despite a well-characterized immune response to adenoviral vectors [ 59 ] and a likely in vivo immune response against Cas9 per se [ 60 ], our work showed that knock-in gene editing via adenoviral vector is efficient enough to persist over time and did not have overt detrimental effects on the animals' health. Our results, taken with an overall lack of mortality in the study, allow the conclusion that adenovirus vector-mediated knock-in was well tolerated in the animals, contrary to a previous report of adenovirus as unsuitable for therapeutic gene editing [ 12 ].…”
Section: Discussionmentioning
confidence: 80%
“…Viral vectors and non-viral nanoparticles are taken up by monocytes and macrophages in various tissues, specifically within the liver and spleen, and the incoming particle and DNA or RNA is sensed by innate immune mechanism. This results in release and activation of pro-inflammatory cytokines 68 . It is thought that AAV vectors provoke weaker innate immune responses than other viral vectors such as Ad or LV 69 , however, at this point no direct comparisons of these vector systems with regards to innate toxicity have been made following IV injection.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions impacting Ad biodistribution upon intravascular delivery have been widely described. Reasons for the low efficacy of Ad5-derived vectors include clearance after opsonization by natural antibodies and complement, as well as sequestration in the liver and spleen mediated by binding with human coagulation factor 10 (FX) and other coagulation factors to HSPG abundant on hepatocytes or scavenger receptors on Kupffer cells [136][137][138]. Since a small portion of the Ad particles injected ip are able to enter the circulation, Ad vectors administered through this route are susceptible to clearance after interacting with blood components and residential macrophages in tissue and in the peritoneal cavity [83,139].…”
Section: Overcoming Physical Barriers To Dissemination Of Oncolytic Amentioning
confidence: 99%